"A cry in the vast dark": Ian Holding's What Happened to Us and the confession of shame. (June 2022) - Marais, Mike
Like much white Zimbabwean writing in the aftermath of the land invasions of 2000, Ian Holding's What Happened to Us concerns itself with the issue of white identity, but does so through its invocation of Zimbabwe's failed policy of racial reconciliation. In this article, I examine this novel's meditation on reconciliation and the possibility of attaining a postcolonial condition that breaks with colonial modes of identity predicated on negating forms of racial difference. I trace, in particular, Holding's use of the confessional mode of writing in his engagement with the idea of reconciliation. Whereas this mode ordinarily focuses on individual guilt, I show that, in Holding's novel, it expresses the collective shame of whites for their separatism, which is presented as a failure of imagination. Throughout, my focus is Holding's recalibration of the confessional mode of writing to accommodate a community perspective, and the implications of this reconceptualization for confession's telos, which is the forgiveness of the individual confessant and, with it, his or her reintegration into community. I argue that the confession of shame, if it is to end with such reintegration or reconciliation, effectively requires the confessant to imagine his or her own death.